THE EFFECTIVENESS OF NUTRITION EDUCATION ON STUNTING PREVENTION BEHAVIOR IN PREGNANT WOMEN IN KAWAY XVI DISTRICT, ACEH BARAT REGENCY - Nanda Julita; Enda Silvia Putri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Stunting is a health problem in the world that has not been completely resolved until now. It is estimated that 22.2% or 150.8 million children under five in the world are stunted. West Aceh is one of the districts in Aceh province which has a high prevalence of stunting, so this is a public health problem. Therefore, it can be stated that the state of Indonesia, especially the province of Aceh and also the district of West Aceh, for stunting has not yet reached the WHO target, which means it is still a public health problem. Objective: to examine the effectiveness of education on prevention of stunting in pregnant women. Research methods: The design used in this study was quasi-experimental with one group pre and post test. The sample in this study amounted to 15 pregnant women. the sample was selected using consecutive sampling. Then tested the difference in knowledge of pregnant women using the Wilcoxon test . Results: the results of the Wilcoxon test showed that there was a significant difference in the knowledge of the respondents after being given education about stunting prevention by the researchers (p-value = 0.002). Conclusion: it can be seen that by providing knowledge education on stunting prevention behavior in pregnant women has very potential results, so it is hoped that the knowledge that has been obtained can be applied to future children. Suggestion: From the results of the study, nutrition education for pregnant women should be carried out several times so that what is conveyed can be received and can be understood properly so that pregnant women understand the importance of adequate nutrition so that stunting does not occur in their future babies.